2011
DOI: 10.1210/me.2011-1160
|View full text |Cite
|
Sign up to set email alerts
|

Residues within the Transmembrane Domain of the Glucagon-Like Peptide-1 Receptor Involved in Ligand Binding and Receptor Activation: Modelling the Ligand-Bound Receptor

Abstract: The C-terminal regions of glucagon-like peptide-1 (GLP-1) bind to the N terminus of the GLP-1 receptor (GLP-1R), facilitating interaction of the ligand N terminus with the receptor transmembrane domain. In contrast, the agonist exendin-4 relies less on the transmembrane domain, and truncated antagonist analogs (e.g. exendin 9-39) may interact solely with the receptor N terminus. Here we used mutagenesis to explore the role of residues highly conserved in the predicted transmembrane helices of mammalian GLP-1Rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 57 publications
5
73
2
Order By: Relevance
“…For example, although GLP-1 Ala 18 was proposed to be located close to Glu 133 of the ECD of GLP1R by photoaffinity labeling (45), the ligand-bound crystal structure of the GLP1R ECD shows a hydrophobic interaction between GLP-1 Ala 18 and Leu 32 of the ECD (20,21). Molecular docking studies with biochemical analyses have suggested possible ligand binding pockets in the GLP1R core domain (47,50,51). However, these modeling approaches failed to provide a common consensus for the ligand binding pocket.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although GLP-1 Ala 18 was proposed to be located close to Glu 133 of the ECD of GLP1R by photoaffinity labeling (45), the ligand-bound crystal structure of the GLP1R ECD shows a hydrophobic interaction between GLP-1 Ala 18 and Leu 32 of the ECD (20,21). Molecular docking studies with biochemical analyses have suggested possible ligand binding pockets in the GLP1R core domain (47,50,51). However, these modeling approaches failed to provide a common consensus for the ligand binding pocket.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the emergence of two class B TM crystal structures (Hollenstein et al, 2013;Siu et al, 2013) and a plethora of mutagenesis (Lopez de Maturana and Donnelly, 2002;Lopez de Maturana et al, 2004;Coopman et al, 2011;Koole et al, 2012a,b;Wootten et al, 2013) and photoaffinity labeling data (Al-Sabah and Donnelly, 2003;Dong et al, 2004Dong et al, , 2007Dong et al, , 2011Chen et al, 2009Chen et al, , 2010Miller et al, 2011;Coin et al, 2013), structurally and functionally important components of the GLP-1R can begin to be predicted and complementary molecular models can be further refined. In this study, we have created a series of mutations at two GLP-1R residues subject to polymorphic variance (amino acids 149 and 333; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A had limited effect on GLP-1 affinity and cAMP formation (Coopman et al, 2011), suggesting that other interactions predominate, at least for activation of this pathway. In the current study, we have modeled a GLP-1 bound form of the full-length receptor that incorporates known distance constraints from published crosslinking studies (Fig.…”
mentioning
confidence: 96%